Corporate governance and food firms' unethical production practices?. Issue 10 (1st October 2018) - Liu, Chia-Yi; Lee, Cheng-Yu; Tsai, Hsin-Ju Stephie
Abstract : Purpose: Although a number of studies have researched food firms' unethical practices, the mechanisms used to prevent these practices remain underexplored from the perspective of corporate governance. As independent directors (IDs) have been viewed as a mechanism to deter corporate misconducts, the purpose of this paper is to investigate the influences of the ratio of IDs on the board, IDs' industrial experience and their participation in corporate governance training courses on food firms' unethical production practices. Design/methodology/approach: This study is based on a sample of 239 firm-year observations in Taiwanese food industries. The Poisson model with fixed effects was used to test the research hypotheses. Findings: The results show that board independence and IDs with food industry expertise were not effective in deterring food firms from unethical production practices. The expected monitoring function of IDs would only realize when they complete a sufficient number of corporate governance training courses. These courses can make IDs aware of their responsibilities and roles in governing firms. Originality/value: This study is the first to identify the effects of corporate governance practices on food firms' unethical production practices. The value of this study may provide food firms practical solutions that enable corporate executives to behave ethically.